2014
DOI: 10.3109/10582452.2014.949336
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Modal Pain Therapy of Fibromyalgia Syndrome with Integration of Systemic Whole-Body Hyperthermia – Effects on Pain Intensity and Mental State: A Non-Randomised Controlled Study

Abstract: Objectives: This controlled study evaluates a multi-modal pain therapy for treating severe progressions of fibromyalgia [FMS] syndrome. The aim is to establish whether the use of multi-modal therapy with inclusion of whole-body hyperthermia represents a useful therapeutic addition to inpatient therapy of FMS syndrome at a high level of chronification. Methods: The study involved 130 patients who fulfilled the criteria of the American College of Rheumatology [ACR] for FMS and whose disease showed severe progre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 52 publications
0
18
0
3
Order By: Relevance
“…Six out of seven studies found statistically significant reductions in depressive symptomology somewhere between 1 and 6 weeks post-intervention. Romeyke [21] did not report significant findings when measuring depressive symptomology using the PHQ-D assessment. Overall 21 study end-points were provided from the studies with significant anti-depressant effects reported for 19; only 2 end-points (H€ uppe) did not reach statistical significance.…”
Section: Resultsmentioning
confidence: 84%
See 2 more Smart Citations
“…Six out of seven studies found statistically significant reductions in depressive symptomology somewhere between 1 and 6 weeks post-intervention. Romeyke [21] did not report significant findings when measuring depressive symptomology using the PHQ-D assessment. Overall 21 study end-points were provided from the studies with significant anti-depressant effects reported for 19; only 2 end-points (H€ uppe) did not reach statistical significance.…”
Section: Resultsmentioning
confidence: 84%
“…PRISMA study flowchart. Overall, our literature search identified 13 studies [11][12][13][14][15][16][17][18][19][20][21][22][23] for further review. After evaluating all studies with the aforementioned criteria, the seven studies [14,15,18,19,[21][22][23] outlined below were selected for further analysis and data extraction.…”
Section: Study Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…With reasons uncertain, there are many varied approaches to treatment. Multimodal treatment under inpatient conditions has proven to be effective for the complex and multilayered pattern of symptoms associated with fibromyalgia 58…”
Section: Background and Purposementioning
confidence: 99%
“…When conventional medical in-hospital procedures are broadened to a holistically orientated patient care, studies show positive effects on the quality outcomes. 16 20 Yet these studies refer to condition without DRGs.…”
Section: Introductionmentioning
confidence: 99%